(untitled) (Eurasian Journal of Engineering and Technology, 2022)
To reduce the cost of corrosion repairs, the need for corrosion-resistant materials has grown. Glass fiber GFRP is an excellent substitute for reinforcing steel in concrete constructions due to its low cost and good corrosion resistance. However, as the production of cement produces a significant amount of CO2, other options are in high demand. Fly ash is one of the replacements used to partially or fully replace cement in concrete mixtures in order to reduce carbon dioxide emissions. In this study, in addition to the conventional concrete, high-volume fly ash concrete with a 50 % cement replacement was used. Although several research studies have used a pull-out method to conduct an investigation of the bond stress–slip behavior of glass fiber polymer (GFRP) and steel bars implanted in high-volume fly ash concrete, no work has been published on the fatigue bond performance of GFRP or steel bars embedded in high volume fly ash concrete using a hinged beam. This paper discusses the experimental testing of eight hinged beams fabricated in accordance with RILEM standards. With reinforcement bars of 10 mm diameter and bond length 10 times of diameter. The test results show that high volume fly ash concrete exhibited good fatigue bond strength better than conventional concrete for steel bars and GFRP bars.